Screening of variables relevant to biomass yield and biopolymer yield in shake-flask fermentation for biopolymer. - Nurul Nadiah, Manap (2009)
The production of biodegradable polymer poly (3-hydroxybutyrate) can be done by the bacteria Cupriavidus necator under depletion of nitrogen source and excess source of carbon. In this research, screening of variables which are involved in the production of PHB was done. The experiment was focusing on determining which variables do not give significant effect toward the production of PHB. The significant effect for each variable which are the agitation rate, temperature, glucose, peptone, disodium hydrogen phosphate, ammonium sulphate, magnesium sulphate and potassium di-hydrogen phosphate were analyzed by using the factor analysis method.Linear models were used to describe the yield as the dependent variable in terms of factors as the independent variables. Starting with the factor corresponding to the smallest eigenvalues and proceeding with factors corresponding to successively bigger eigenvalues, factors were dropped and the mean square error of the resulting linear model is compared with the mean square error of the full model using the F test. For the linear regression involving uncorrelated variables for biomass yield, concentration of di-sodium phosphate and potassium dihydrogen phosphate respectively gave significant effect toward the yield. In addition, for biopolymer yield, the concentrations of peptone, ammonium sulphate, disodium hydrogen phosphate and potassium dihydrogen phosphate respectively give a significant effect toward the yield.